2016
DOI: 10.1007/s11999-016-4894-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinician and Patient-reported Outcomes Are Associated With Psychological Factors in Patients With Chronic Shoulder Pain

Abstract: BackgroundValidated clinician outcome scores are considered less associated with psychosocial factors than patient-reported outcome measurements (PROMs). This belief may lead to misconceptions if both instruments are related to similar factors.QuestionsWe asked: In patients with chronic shoulder pain, what biopsychosocial factors are associated (1) with PROMs, and (2) with clinician-rated outcome measurements?MethodsAll new patients between the ages of 18 and 65 with chronic shoulder pain from a unilateral sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 45 publications
7
37
0
1
Order By: Relevance
“…Given the substantial governmental investment, its computer adaptive testing, and assessments that capture each of these health domains, PROMIS is positioned to become a consensus patient-reported outcome. The relationship of PROMIS mental health scores and physical function scores in our study appear consistent both in direction and magnitude when compared to previous studies using legacy health measures thus adding data toward the validity of PROMIS Anxiety when administered as part of routine orthopedic practice[5; 19; 20; 23; 24; 29; 30]. Our data have uniquely assessed the clinical use of the PROMIS CAT’s and distinguished that Anxiety scores demonstrate stronger correlations with patient-reported Physical Function and Pain Interference than Depression scores do.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Given the substantial governmental investment, its computer adaptive testing, and assessments that capture each of these health domains, PROMIS is positioned to become a consensus patient-reported outcome. The relationship of PROMIS mental health scores and physical function scores in our study appear consistent both in direction and magnitude when compared to previous studies using legacy health measures thus adding data toward the validity of PROMIS Anxiety when administered as part of routine orthopedic practice[5; 19; 20; 23; 24; 29; 30]. Our data have uniquely assessed the clinical use of the PROMIS CAT’s and distinguished that Anxiety scores demonstrate stronger correlations with patient-reported Physical Function and Pain Interference than Depression scores do.…”
Section: Resultssupporting
confidence: 87%
“…First, recognizing the relatively high prevalence of anxiety in patients seeing orthopedic surgeons is needed as anxiety is a modifiable disorder that, if treated, can directly impact surgical outcomes in a positive manner. To that end, heightened anxiety is associated with worse patient-reported function, greater pain, and less treatment satisfaction with musculoskeletal conditions [3; 19-27]. Second, although Anxiety and Depression may each be important to understand, if surgeons were only able to collect a single PROMIS assessment of mental health, the reduced floor effect may support the prioritization of PROMIS Anxiety over Depression.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder pain can be negatively affected by psychological factors (ie, anxiety, depression, and catastrophizing symptoms), whereas shoulder disability is influenced by psychological and social factors (ie, language and professional qualification). 32 These factors were not evaluated in the current study and should be considered in future research investigating SAPS.…”
Section: Discussionmentioning
confidence: 95%
“…Patient reported outcome measures are an important research tool for evaluating healthcare outcomes, however they are dependent on numerous factors. Studies evaluating shoulder pain outcome scores in a primarily degenerative rotator cuff tear population found that psychosocial factors such as anxiety, catastophising and depression as well as social factors such as education, language and professional qualification were associated with poorer outcome scores and less perceived improvement in function [ 18 , 19 ]. Various factors have been shown to impact upon the outcome of rotator cuff repair surgery as discussed in the introduction.…”
Section: Discussionmentioning
confidence: 99%